Towards an Early Warning System for cotton pests in Benin using long-term and multilocal observational data - (:unkn) unknown (My University, 2023)
Controlling pest populations in cotton fields is crucial to reduce yield losses due to plant damage. However, knowing the economic, environmental and agronomical issues related to the systematic use of chemical insecticides, it is urgently needed to better assist spraying decisions based on the development of an Early Warning System. In Benin, one of the major cotton producers in West Africa, a comprehensive annual monitoring of the incidence of key pests has been implemented for more than ten years. Here, we propose to use these long-term and multilocal observational data to (1) better understand the relationships between environmental variables, including climate, landscape context, but also crop management, and intra- or inter-annual pest population dynamics within the cotton-growing area, and to (2) better predict the risk of yield loss due to key pests as to better target interventions. As a perspective, we suggest developing standardized data collection and management throughout the West-African cotton-growing area for areawide pest management.
Keywords: African Research